2011
DOI: 10.2743/jve.15.1
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Koala Retrovirus

Abstract: A novel Gammaretrovirus, named Koala retrovirus (KoRV) was identified in koalas in 2000. Subsequent testing has shown that KoRV appears to be widespread throughout the wild koala population in Australia. KoRV is apparently unique in that it is the only known example of an exogenous retrovirus which is actively undergoing the process of endogenisation. While there is currently little direct evidence that KoRV causes overt disease in koalas, it is possible or even likely that KoRV infection plays a significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
1
13
1
Order By: Relevance
“…KoRV-A was detected in all northern koalas tested and in 4 out of 11 Victorian koalas (Fig. 3B and Table 3), consistent with previous reports that KoRV had become endogenous in koalas in northern Australia (6,7,9,10). In contrast, KoRV-J was detected in 67.5% of northern koalas but not in southern (Victorian) koalas (Fig.…”
Section: Lacz(korv-j) and Lacz(felv-a) Infected Mdtf Cells Expressingsupporting
confidence: 75%
See 1 more Smart Citation
“…KoRV-A was detected in all northern koalas tested and in 4 out of 11 Victorian koalas (Fig. 3B and Table 3), consistent with previous reports that KoRV had become endogenous in koalas in northern Australia (6,7,9,10). In contrast, KoRV-J was detected in 67.5% of northern koalas but not in southern (Victorian) koalas (Fig.…”
Section: Lacz(korv-j) and Lacz(felv-a) Infected Mdtf Cells Expressingsupporting
confidence: 75%
“…A correlation between these neoplastic diseases and the plasma viral load of KoRV, the suspected causative agent, has been reported (6,7). In addition, many koalas suffer from opportunistic infectious diseases, such as chlamydiosis and cryptococcosis, indicating that KoRV may also induce immunosuppression (3,(8)(9)(10). To clarify the relationship between KoRV and these diseases, it is necessary to accumulate more epidemiological and virological data.…”
mentioning
confidence: 99%
“…Associations with infectious disease are equivocal (Simmons, 2011;Tarlinton et al, 2005), though this might be due to the multi-factorial nature of disease, especially in populations of free-ranging animals. The most direct evidence for immunomodulatory effects of KoRV comes from the effect of purified KoRV on cytokine expression by cultured human PBMCs, whereby it induced elevated expression of interleukin-6 (IL-6), IL-10, growth-related oncogene (GRO) and monocyte chemotactic protein-1 (MCP-1) (Fiebig et al, 2006).…”
Section: Is Korv Immunomodulatory In Koalas?mentioning
confidence: 99%
“…It has previously been suggested that southern koalas suffer less from all forms of disease (including chlamydiosis) than their northern (QLD, NSW) counterparts. (Simmons et al, 2011).…”
Section: Discussionmentioning
confidence: 99%